State, justice, and recognition - Filgueiras, Fernando (2010)
This article investigates, from a normative critique, the liberal perspective and the communitarian perspective of the concept of justice, speculating on the role of the state in contemporary democracies. The investigation of the liberal perspective and the communitarian perspective of the concept of justice tend to indicate a republican critique of the depoliticisation process promoted by the concept of political justice and social justice. This article advocates a political conception of justice based on the existence of a republican state and the popular image of the origin of constitutional principles and rules.